Prognostic significance of viable tumor size measurement in hepatocellular carcinomas after preoperative locoregional treatment - Hwang, Yoon Jung; Lee, Youngeun; Park, Hyunjin; Lee, Yangkyu; Lee, Kyoungbun; Kim, Haeryoung (Journal of pathology and translational medicine, 2021)
Background: Preoperative locoregional treatment (LRT) for hepatocellular carcinoma (HCC) often induces intratumoral necrosis without affecting the overall tumor size, and residual viable tumor size (VTS) on imaging is an important clinical parameter for assessing post-treatment response. However, for surgical specimens, it is unclear whether the VTS would be more relevant to prognosis compared to total tumor size (TTS).Methods: A total of 142 surgically resected solitary HCC cases were retrospectively reviewed. The TTS and VTS were assessed by applying the modified Response Evaluation Criteria in Solid Tumors method to the resected specimens, and correlated with the clinicopathological features and survival.Results: As applying VTS, 13/142 cases (9.2%) were down-staged to ypT1a. Although the survival analysis results for overall survival according to TTS or VTS were similar, VTS was superior to predict disease-free survival (DFS; p = .023) compared to TTS (p = .08). In addition, multivariate analysis demonstrated VTS > 2 cm to be an independent predictive factor for decreased DFS (p = .001). In the subpopulation of patients with LRT (n = 54), DFS in HCCs with TTS or VTS > 2 cm were significantly shorter than those with TTS or VTS ≤ 2 cm (p = .047 and p = .001, respectively). Interestingly, HCCs with TTS > 2 cm but down-staged to VTS ≤ 2 cm after preoperative LRT had similar survival to those with TTS ≤ 2 cm.Conclusions: Although the prognostic impact of tumor size was similar regardless of whether TTS or VTS was applied, reporting VTS may help to increase the number of candidates for surgery in HCC patients with preoperative LRT.